Factors influencing the caregiver burden for family caregivers of people with moderate-to-severe dementia: A structural equation modeling analysis - Hong Qi; Jingjing Ban; Nana Wang; Tian Yao; Li Li; Shan Tang (PLoS ONE, 2026)
Background Dementia poses an increasingly serious public health challenge worldwide, particularly in China, where home-based care remains the primary form of management. Family caregivers of older adults with moderate-to-severe dementia often experience a substantial caregiving burden, which can adversely affect both their own well-being and that of the patients. Objective This study aimed to examine the level of caregiver burden among family caregivers of older adults with moderate-to-severe dementia and to explore the relationships between patient activities of daily living (ADL), quality of life (QoL), depression severity, caregiver QoL, depression severity, and caregiver burden. Methods A cross-sectional study in 22 tertiary general hospitals in Shanxi Province, China, involved 529 dyads of older adults with moderate-to-severe dementia and their family caregivers. Caregivers completed the Zarit Burden Interview, the Patient Health Questionnaire-9, and the World Health Organization Quality of Life–Brief Version. Older adults completed the Patient Health Questionnaire-9, the Activity of Daily Living Scale, and the Quality of Life in Alzheimer’s Disease scale. Structural equation modeling evaluated relationships among patient ADL, QoL, depression severity, caregiver QoL, depression severity, and caregiver burden. Results Patient QoL, ADL, and caregiver QoL had direct negative effects on caregiver burden, whereas patient and caregiver depression severity had direct positive effects on caregiver burden. Meanwhile, caregiver QoL partially mediated the relationships between patient QoL, depression severity, ADL, caregiver depression severity, and caregiver burden. Conclusion The results indicate that higher patient QoL, better patient ability in ADL, higher caregiver QoL, and lower levels of depressive severity in both patients and caregivers are associated with reduced caregiver burden. Healthcare professionals should implement family-centered, comprehensive interventions to alleviate caregiver burden.